ANALISIS SPASIAL SUMBERDAYA ALAM PERKEBUNAN KARET RAKYAT KOTA BANJARBARU DENGAN MENGGUNAKAN DATA PENGINDERAAN JAUH - Kasumahadi Kasumahadi; Wahyuni Ilham; Abdi Fithria; Gunawansyah Gunawansyah (Universitas Lambung Mangkurat, 2013)
The processing of remote sensing and field survey data that applying Geographic Information System (GIS) was important to do in order to collect the basic data and an accurate information about rural rubber plantation natural resources. The !st threemonthly 2013 statistical report of Banjarbaru City plantation, showed that rural rubber plantation was 986 Ha’s width. Thus data, comprehensively not adequate to answer the exact/certain width of rural rubber plantation in Banjarbaru. So, it was considered necessarily to complete them with such Geographic Information. This research was aimed (1) to determine the exact width of rural rubber plantation area; and (2) to make a thematic map of rural rubber plantation natural resources. This research was conducted in Cempaka village, Banjarbaru City, south Kalimantan Province. This research was occupied by collecting important data and information, then analyzed them by using GIS. The primary data were collected by taking coordinate points on field with Global Positioning System (GPS) tool, and analyzed them by using GIS spatial analysis. The result showed that the width of rural rubber plantation based on year 2007 quickbird survey was 1.357,82 Ha which withdrawn in the map of rural rubber plantation natural resources in Cempaka Village, Banjarbaru City. Thus, according to year 2010 alos-avnir mulispektral classification resulted that the width was 999 Ha, withdrawn in the landcover map of Cempaka Village banjarbaru City. We might conclude that the width of rural rubber plantation in Cempaka Village based on quickbird survey in 2007 was 419,82 Ha larger than 938 Ha statistical data of rural rubber plantation in Cempaka, and it was 61 Ha larger if compared with 2010 alos-avnir mulispektral classification. Those data were included in two (2) different map of rural rubber plantation natural resources in Cempaka Village Banjarbaru City.